Study on subsidence evolution induced by coal mining under highway based on finite element simulation - Guoxi Cheng; Huibin Liu; Fengli Li; Teng Nie; Qiang Wang; Chuang Peng (Energy Exploration & Exploitation)
Accurate estimation of overlying strata subsidence and surface deformation caused by coal extraction is crucial for assessing the impact of mining activities on surface infrastructure. In this study, we investigated the subsidence evolution of overlying strata and ground surface induced by underground mining using finite element simulation and focus on a mining district in the Yu-Heng mining area of the central Ordos Basin and then, the influence of underground longwall mining on the surface roads was evaluated. A three-dimensional geological model of the mining district was constructed, considering the actual stratum structures and the deterioration effect of water on rock mechanical properties. The whole coal mining process was simulated to predict the evolution of the subsidence basin at different mining stages, and the surface deformation characteristics caused by coal mining were calculated. Results showed that the subsidence characteristics by numerical simulation were highly consistent with the records of surface subsidence in the adjacent areas, indicating that the constructed geological model can accurately reflect the actual geological conditions and the deformation behaviors of overlying strata. A comparative study revealed that the mechanical properties of the generalized layers determined by processing the mechanical parameters of dry core samples will be much higher than those of the natural strata under the in situ water-saturated condition, and then the subsidence caused by coal mining will be significantly underestimated. Thus, the water-induced mechanical property deterioration of overlying strata must be fully considered when constructing geological models.